Indicadores antecedentes do complexo metalmecânico brasileiro - Conceição, Marcus Vinícius de Souza Almeida (Universidade do Vale do Rio dos Sinos, 2016)
This study aims, in the approach to real business cycles, draw two composite indicators, antecedent and coincident to the Brazilian metal-mechanic complex. It delimits and is characterized as metal-mechanic complex industrial activities in sections 24; 25; 26; 27; 28; 29; 30 of CNAE 2.0. The development of indicators was guided through adapting the methodology proposed by the OECD in 2012 for the preparation of composite indicators. According to the routines revealed by this methodology were collected and treated in 1026 time series with monthly data covering the period 1994 to 2015. These data were submitted to statistical treatment filtering and evaluation, application of X-12 filters, HP, CF FD, conducting Cross-Correlation tests using ARIMA models and PROBIT. As a result, produced an index (I-MM) to follow in real time the performance of the metal-mechanic complex and three leading indicators, these comprising a probability of occurrence of an event, which stipulate short-term scenarios (IACP-MM) and medium term (IAMP1-MM, IAMP2-MM)
Keywords: Ciclos econômicos; Complexo metalmecânico; Indicadores antecedentes; Business cycle; Metal-mechanic complex; Composite leading indicators; JEL classification: Q19, O40, C43; ACCNPQ::Ciências Sociais Aplicadas::Economia